Parental Attitudes and Beliefs Surrounding Play Among Predominantly Low-income Urban Families: A Qualitative Study. Issue 8 (October 2019) - Shah, Reshma; Gustafson, Erika; Atkins, Marc
ABSTRACT: Objective: Parents' perceived benefits and barriers to participation in cognitively stimulating activities may help explain why income-related discrepancies in early and frequent participation in such activities exist. We sought to develop an improved understanding of attitudes and beliefs surrounding play among families who live in predominantly low-income urban communities. Methods: Using qualitative methods, focus groups were conducted with parents of children 2 weeks to 24 months of age who attended a primary care clinic serving predominantly low-income urban communities. Discussions were recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Thirty-five parents participated in 6 focus groups. Participants were 61% female and 94% nonwhite; 71% had children who received public health insurance. Analyses revealed 7 major themes that mapped onto the Health Belief Model's core domains of perceived need, barriers, and cues to action: (1) play as important for developing parent-child relationships, (2) toy- and media-focused play as important for developmental and educational benefit, (3) lack of time due to household and work demands, (4) lack of knowledge regarding the importance of play, (5) media-related barriers, (6) need for reminders, and (7) need for ideas for play. Conclusion: Caregivers of young children describe many important benefits of play, yet they have misconceptions regarding use of toys and media in promoting development as well as notable barriers to participating in play, which may be opportunities for intervention. Public health programs may be more effectively implemented if they consider these attitudes to develop new or refine existing strategies for promoting parent-child learning activities. Abstract : This article has supplementary material on the web site: www.jdbp.org.